PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SDN 46 MEMBURA - Irma Yunita; Rahmat; Saleha (STKIP Subang, 2026)
This research is motivated by the low learning outcomes of Pancasila Education of fourth-grade students of SDN 46 Membura due to the learning process still being dominated by lecture methods so that students are less active, less courageous in expressing opinions, and less involved in the learning process. Of the 22 students, many still have not reached the KKTP of 75%. This study aims to determine the improvement in learning outcomes of Pancasila Education of fourth-grade students of SDN 46 Membura through the application of the Make a Match learning model. The research method used is Classroom Action Research (CAR) with the Kemmis and Mc Taggart model which consists of the planning, action implementation, observation, and reflection stages. The research was conducted in two cycles with 22 students as research subjects. The results of the study indicate that the application of the Make a Match learning model can improve student learning outcomes. In the pre-action stage, student learning completeness only reached 23%, then increased to 64% in cycle I and increased again to 91% in cycle II. In addition, student activeness and participation during the learning process also increased. Thus, it can be concluded that the application of the Make a Match learning model can improve the learning outcomes of Pancasila Education for fourth grade students at SDN 46 Membura and create a more active, enjoyable, and meaningful learning atmosphere for students.